Invasive Forest Insects, Introduced Forest Trees, and Altered Ecosystems Ecological Pest Management in Global Forests of a Changing World - Paine, Timothy D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Demand for timber and fibre continues to grow and is being met by increased reliance on plantation forestry. Many of the plantations that are being grown around the globe are non-native species that have characteristics of rapid growth and good commercial qualities. In some cases, the high rates of production are a result of the absence of native herbivore and diseases. This limited pest status is threatened as pest species move around the globe. At the same time there is concern about threats of these non-native plantation species on native communities and the impact of changing climates on forest productivity. This volume explores many of these issues for the first time.
Are Island Forests Vulnerable to Invasive Defoliators? -- Changing Forest Communities: Role of Tree Resistance to Insects in Insect Invasions and Tree Introductions -- Southern Hemisphere Exotic Pine Plantations Threatened by Insect Pests and their Associated Fungal Pathogens -- Native Insects Colonizing Introduced Tree Species—Patterns and Potential Risks -- Biological Pest Control in Mix and Match Forests -- Impacts of Insects in Forest Landscapes: Implications for Forest Health Management -- Insect Populations In Relation To Environmental Change In Forests Of Temperate Europe -- Synecology Of Wasmannia Auropunctata, An Invasive Ant Species (Hymenoptera: Formicidae), Continuous And Fragmented Areas In The Brazilian Atlantic Forest -- Changing Relationships Among Biodiversity, Management, And Biosecurity In Managed And Unmanaged Forests -- 10.
Keywords: Plant science; Botany; Entomology; Forestry; Ecology .; Plant Sciences; Entomology; Forestry; Ecology